Development of biorelevant simulated salivary fluids for application in dissolution testing - Gittings, Sally (2017)
Conventional adult dosage forms such as tablets and capsules are often not suitable for the paediatric and geriatric population due to either swallowing difficulties or a requirement for tailored dosing to meet individual needs. Alternative oral formulations such as orally disintegrating tablets (ODTs) are available; however these usually require the incorporation of taste masking techniques. One approach to taste masking is to reduce contact between the bitter active pharmaceutical ingredient (API) and taste buds. This may be achieved by hindering release in the oral cavity using reverse enteric polymeric coatings.